Spatial Deflection of Parallel Hydraulic Fractures and Induced Shear Stress Disturbance Under Different Perforation Cluster Spacing Considering Thermal Effects - Wang, Yongliang; Liu, Nana; Cui, Yishuo; Liu, Xuguang (Frontiers in Built Environment, 2022)
Reliable estimation of fracture network length and morphology in hydrofracturing is crucial for controlling and optimizing fracturing effects. Hydraulic fracture propagation will be affected by a variety of factors to produce deflection, resulting in different fracture network morphology. To study the spatial deflection behaviours of multiple parallel hydraulic fractures, three-dimensional engineering-scale numerical model for multistage fracturing is established to study the induced shear stress disturbance and unstable spatial propagation behavior of hydraulic fractures under different perforation cluster spacing. In the model, the thermal diffusion, fluid flow and deformation of rock between the rock matrix and fluid in pores and fractures are considered to describe the thermal-hydro-mechanical coupling. In this study, the results show that the thermal effect between fracturing fluid and rock matrix is an important factor affecting fracture propagation, and thermal effects can increase induced shear stress area and promote fracture propagation. The induced shear stress disturbance caused by fracture propagation is superimposed in multiple fractures, resulting in stress shadow effect and spatial deflection of parallel fractures. The stress shadow areas and the spatial deflection of parallel hydraulic fractures will increase with the decrease of multiple perforation cluster spacing.